PENGARUH KOMPETENSI, INDEPENDENSI DAN ETIKA TERHADAP KINERJA APARAT PENGAWAS INTERN PEMERINTAH (APIP) INSPEKTORAT DAERAH KABUPATEN PARIGI MOUTONG - Jasman, Jasman (Katalogis, 2016)
This study aims to seek and analyze the influence of competency, independency, and ethic on the performance of Internal Governmental Supervisor at The Regional Inspectorate Office of Parigi Moutong District, both simultaneously and partially. Primary and secondary data are collected from questionnaires, interviews, and document study and analyzed with multiple linear regressions analysis. The result indicates that: 1) competency, independency, and ethic simultaneously have significant influence on the performance of Internal Governmental Supervisor at The Regional Inspectorate Office of Parigi Moutong District; 2) Competency has significant influence on the performance of Internal Governmental Supervisor at The Regional Inspectorate Office of Parigi Moutong Distric; 3) Independence has significantÂ  influence on the performance of Internal Governmental Supervisor at The Regional Inspectorate Office of Parigi Moutong District; 4) ethic has significant influence on the performance of Internal Governmental Supervisor at The Regional Inspectorate Office of Parigi Moutong District.